Review/ Epidemiology and natural history of Chronic Hepatitis C Virus infection - Rawaa Najim Abdullah; Mustafa jawad kadham; Amran M. AL-Erjan (Genius Publishing Group, 2022)
It is believed that between 130 and 170 million individuals throughout the globe are infected with HCV. China has the highest number of people living with HCV of any nation in the world, with over 1% of the population afflicted (29.8 million). The burden of advanced liver disease varies greatly from country to country as a direct consequence of the disparities in HCV incidence in the past and HCV prevalence in the present, as well as the relatively gradual progression of HCV sickness. Over the next two decades, the prevalence of HCV-related cirrhosis and hepatocellular carcinoma (HCC) in nations with a high prevalence of HCV or a recent incidence peak would continue to rise. Acute HCV infection is hard to identify since the illness is often symptomless and at-risk groups are often marginalised. Approximately 25% of individuals with acute HCV infection clear the virus spontaneously, with higher rates among those with favourable IL28B genotypes, acute symptoms, and women. Chronic HCV infection, which increases the risk of hepatic fibrosis, cirrhosis, and HCC, affects the remaining 75% of patients. Although chronic hepatitis C tends to proceed slowly in its first two decades, ageing and co-factors like high alcohol consumption and HIV co-infection might speed up the disease during this time.
Keywords: HCV; chronic; epidemiology; cirrhosis